Pengaruh Profitabilitas, Solvabilitas Dan Auditor Switching Terhadap Audit Delay Dengan Umur Perusahaan Sebagai Variabel Moderasi - Ainayya Silmi Kaffah Marianto; Fatchan Achyani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the effect of profitability, solvency, and auditor switching on audit delay with firm age as a moderating variable. A quantitative approach was employed using secondary data derived from audited financial reports of property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. A purposive sampling method was used, resulting in a sample of 76 companies. The data were analyzed using Moderated Regression Analysis (MRA), preceded by descriptive statistics and classical assumption tests. The findings reveal that profitability has a significant effect on audit delay, indicating that firms with higher profitability tend to complete their audits more promptly. In contrast, solvency and auditor switching do not significantly affect audit delay. Furthermore, firm age does not moderate the relationship between profitability, solvency, or auditor switching and audit delay.